The Psalms as Poems: A Case Study of Psalm 136 - Dada, Samuel Ayodele; Owoeye, Omolara Kikelomo (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The paper is an in-depth study of the one hundred and thirty-sixth Psalm of the Holy Bible from a linguistic lens view. Using a stylo-rhetorical approach to the analysis of the contents of this Psalm, the study discovers that the style and contents of the data are akin to that of many poetic works right from the time of English poetry in medieval times. Psalm 136 is essentially a ballad in terms of its tragic content. The story telling, tragic essence and lyrical content of the Psalm all combined to establish its poetic substance. The conclusion of the work is that Psalm 136, though written on and for religious worship, qualifies to be described as poetry.